The Current Monetary and Credit Policy of Russia in View of the Theory of Money Malfunction - T. S. Novashina (Вестник Российского экономического университета имени Г. В. Плеханова, 2019)
The present day paradigm of monetary and credit policy in Russia was designed by the national monetary authority only a decade ago. In this period of time the economic theory within the frames of public information space was discussing the problem expediency and possibility of Russian banking system passing over to the regime of inflation targeting. At the same time top management of the Bank of Russia in its practical work was constantly discussing the task of potential passing over to the floating rate of the national currency as a precondition for introducing the regime of inflation targeting. But as long as mid-2014 the introduction of the floating rate of the national currency was postponed by top management of the Bank of Russia. The principle reason was the fact that national economy and national currency were not ready to face and stand the test. But in spite of evident counter indications this test took place. It should be mentioned that passing over of the national currency to the regime of free floating was introduced by the Bank of Russia before the appointed time. The article studies key challenges and contradictions of the present day monetary and credit policy in Russia, which would not allow it to increase its efficiency. It shows that these problems and contradictions are stipulated both by system vices of the present concept of monetary and credit policy in Russia and specific features of its designing and realizing by the Bank of Russia, by peculiar decisions made by the Board of Directors, specific understanding on the part of top management and executives of institutional, instrumental and procedure components of the transmission mechanism, including specific understanding of the essence and nature of inflation, i.e. the subject of management within the frames of the present monetary and credit policy in Russia. The author puts forward and substantiates the hypothesis that nature of inflation  is  connected  with  money  malfunction.  Practical  recommendations  were  provided  aiming  at  raising efficiency of monetary and credit policy in Russia. The expediency of status revision and functional reforms of the National Finance Board was shown.